2019
DOI: 10.3847/1538-4357/ab089c
|View full text |Cite
|
Sign up to set email alerts
|

A MegaCam Survey of Outer Halo Satellites. VII. A Single Sérsic Index versus Effective Radius Relation for Milky Way Outer Halo Satellites* †

Abstract: In this work, we use structural properties of the Milky Way's outer halo (R G >25 kpc) satellites (dwarf spheroidal galaxies, ultra-faint dwarf (UFD) galaxies and globular clusters (GCs)) derived from deep, wide-field, and homogeneous data to present evidence of a correlation in the Sérsic index versus effective radius plane followed by a large fraction of outer halo GCs and satellite dwarf galaxies. We show that this correlation can be entirely reproduced by fitting empirical relations in the central surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
1
7
0
1
Order By: Relevance
“…The structural parameters of the bulge of NGC 5474 are consistent with those of pseudo-bulges (Kormendy & Kennicutt 2004, Fisher & Drory 2008, and indeed it is classified as such by Fisher & Drory (2010). It is interesting to note that these parameters are also fully compatible with the scaling laws of dwarf galaxies (see, e.g., Côté et al 2008, Lange et al 2015, Bellazzini et al 2017, Marchi-Lasch et al 2019. In particular, the absolute integrated magnitude, the stellar mass, and the effective radius of the bulge are quite similar to those of NGC 205, a nucleated dwarf elliptical satellite of M 31 (M V = −16.5 ± 0.1, M = 3.3 × 10 8 M , assuming M/L V = 1.0, and R e = 445 ± 25 pc (circularised), from McConnachie 2012).…”
Section: Surface Photometrymentioning
confidence: 52%
“…The structural parameters of the bulge of NGC 5474 are consistent with those of pseudo-bulges (Kormendy & Kennicutt 2004, Fisher & Drory 2008, and indeed it is classified as such by Fisher & Drory (2010). It is interesting to note that these parameters are also fully compatible with the scaling laws of dwarf galaxies (see, e.g., Côté et al 2008, Lange et al 2015, Bellazzini et al 2017, Marchi-Lasch et al 2019. In particular, the absolute integrated magnitude, the stellar mass, and the effective radius of the bulge are quite similar to those of NGC 205, a nucleated dwarf elliptical satellite of M 31 (M V = −16.5 ± 0.1, M = 3.3 × 10 8 M , assuming M/L V = 1.0, and R e = 445 ± 25 pc (circularised), from McConnachie 2012).…”
Section: Surface Photometrymentioning
confidence: 52%
“…Here we consider all stellar systems as a single class aiming not to distinguish between globular clusters and dwarfs. Our moti v ation is two-fold: first, these systems have a similar range in stellar mass, and second, as pointed out by Marchi-Lasch et al ( 2019 ), there are similarities between structural properties of ultra faint dwarfs and low-surface brightness GCs. This leads us to distinguish three different populations, the high-surface brightness (HSB-GCs, with log (SB/ L pc −2 ) > 2), the low-surface brightness (LSB-GCs, with log (SB/ L pc −2 ) < 2) globular clusters (see Fig.…”
Section: Data a N D D E R I V E D O R B I Ta L Pa R A M E T E R Smentioning
confidence: 87%
“…• For the MW satellites, we primarily use the homogeneous analysis from the Megacam Survey of Outer Halo Objects (Muñoz et al 2018a,b;Marchi-Lasch All three of these data sets were observed with CFHT/MegaCam. H21 and PAn-dAS used the g, i−bands and the MSOHO dataset used the g, r−bands (supplemented with some additional DECam observations in equivalent filters).…”
Section: Sample Definitionmentioning
confidence: 99%